Is It Appropriate to Use Restorative Justice in Cases of Domestic Violence? - Schmidt, Laura (Magyar Rendészet, 2023)
Domestic violence (DV) is sometimes called a hidden crime because in many cases victims do not report the offence to the police. DV includes child abuse, intimate partner violence and elder abuse and comes in many forms, such as physical, sexual, emotional or financial abuse.3 Using restorative justice (RJ) methods in cases of DV is a highly controversial topic.4 However, in many countries around the world restorative practices are used in these cases with appropriate safeguarding in place.5 The aim of this article is to explore the different types of RJ methods and the different types of DV cases where these methods might be used with the potential benefits and challenges being discussed. Relevant articles and case studies were analysed to present previously conducted research on the topic of DV and RJ. The available literature shows that certain RJ practices are appropriate in certain types of DV cases but they need to be evaluated on an individual basis as these types of cases are very complex and need to be screened thoroughly before any kind of intervention. However, in addressing the concerns surrounding the use of RJ in DV cases, it is vital to listen to the victims themselves, by first giving them a voice. In conclusion, professionals working with victims and offenders of DV cases need to work more closely with others who work in RJ in order to make the process safer and to utilise the potential benefits of the process.